The effectiveness of multimedia and computer-assisted activities in the teaching of Afrikaans as a second language. - Basson, Irene (My University, 2013)
Teachers are increasingly aware of the technological world in which their students live. They are aware that the use of computers affects the motivation and attitudes of learners. There has also recently been governmental pressure to integrate ICT in the teaching and learning at school level. The question remains how exactly these technologies should be implemented, particularly to aid in the acquisition of a second language. This study investigates if the use of CALL in the teaching of second language Afrikaans has affected the attitudes and motivation of learners and if it had any effect on the results they achieved. A comparative study was conducted with a group Grade 11 learners in which they completed a series of research tasks that included no technology or computerrelated input. The same group was also exposed to lessons with a computer-assisted approach, where a series of comparative research tasks were completed with the use of technology. The group completed reflective questionnaires on the tasks they had completed. The sets of tasks were analyzed and compared to each other and the reflective questionnaires were analyzed and general trends and findings were noted. The findings in this study suggests that learners respond well to computer-assisted tasks and that there is a marked improvement in attitude and motivation when they are exposed to technology in the second language classroom. Furthermore it is evident that the shift in motivation contributes to an overall improvement of their results, which in computerassisted tasks are on average 8%-12% higher.
Keywords: Afrikaans language--Study and teaching (Secondary)--South Africa--Foreign speakers.; Media programs (Education)--South Africa.; Computer-assisted instruction--South Africa.; Second language acquisition.